2020
DOI: 10.1126/sciadv.aba1685
|View full text |Cite
|
Sign up to set email alerts
|

Dermal exosomes containing miR-218-5p promote hair regeneration by regulating β-catenin signaling

Abstract: The progression in the hair follicle cycle from the telogen to the anagen phase is the key to regulating hair regrowth. Dermal papilla (DP) cells support hair growth and regulate the hair cycle. However, they gradually lose key inductive properties upon culture. DP cells can partially restore their capacity to promote hair regrowth after being subjected to spheroid culture. In this study, results revealed that DP spheroids are effective at inducing the progression of the hair follicle cycle from telogen to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(126 citation statements)
references
References 57 publications
2
123
1
Order By: Relevance
“…However, DPC is not a reliable and expandable cell source for large-scale production of EVs. Furthermore, Cheng et al revealed that miR-218-5p-overexpressed exosomes accelerated the onset of anagen, and DPC spheroid culture provided a benificial avenue for cell therapy [ 31 ]. The authors also mentioned that the lack of hormone-related or disease-related hair loss model needed to be filled up in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, DPC is not a reliable and expandable cell source for large-scale production of EVs. Furthermore, Cheng et al revealed that miR-218-5p-overexpressed exosomes accelerated the onset of anagen, and DPC spheroid culture provided a benificial avenue for cell therapy [ 31 ]. The authors also mentioned that the lack of hormone-related or disease-related hair loss model needed to be filled up in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, DPC is not a reliable and expandable cell source for large-scale production of EVs. Furthermore, Cheng et al revealed that miR-218-5p-overexpressed exosomes accelerated the onset of anagen, and DPC spheroid culture provided a beni cal avenue for cell therapy [31] . The authors also mentioned that the lack of hormone-related or disease-related hair loss model needed to be lled up in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that EVs derived from mesenchymal stem cells (MSCs) can be used for stem cell replacement therapy [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In most cases, it is not clear which component of the unmodified EVs exerts curative effects.…”
Section: Therapeutic Application Of Natural Evs As Cell Substitutesmentioning
confidence: 99%
“…MSC-derived EVs reduce radiation-induced lung injury through miRNA-214-3p [13]. Replacing autologous cells with EVs derived from hair follicle papillary cell spheres can promote hair growth [14]. Human umbilical cord mesenchymal stem cell-derived exosomes (UMSC-Exo) can inhibit pyrolysis and repair muscle ischemic injury by releasing circular RNA circHIPK3 [15].…”
Section: Evs Derived From Stem Cells and The Damage Repair And Regenementioning
confidence: 99%
See 1 more Smart Citation